Low hydrogen type covered metal arc welding electrode
Patent Information
- Application Number
- JP2021061509
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2041-03-31
Smart Images

Figure 0007651355000001 
Figure 0007651355000002 
Figure 0007651355000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a low-hydrogen covered metal arc welding electrode, and more particularly to a low-hydrogen covered metal arc welding electrode having improved resistance to moisture absorption and to sheath-falling off. [Background technology]
[0002] Low-hydrogen covered electrodes have good arc stability, excellent crack resistance and weld metal toughness, and are therefore widely used in areas with strong restraint and for welding high-tensile steel.
[0003] On the other hand, with the recent increase in the size of welded structures, there is a demand for higher strength steel materials. However, as the strength increases, management to prevent weld cracks becomes important in welding work, and in particular, to obtain a covered metal arc welding rod with excellent crack resistance, the main condition is that the diffusible hydrogen of the weld metal is extremely low. In order to maintain the characteristics of the low-hydrogen covered metal arc welding rod, it is generally dried at 300 to 400 ° C for about 30 to 60 minutes before use, and stored in a container that can maintain a temperature of 100 to 150 ° C, from which it is taken out and used. If the rod is left in the air before use, it will absorb moisture depending on the environmental conditions, and if welding is performed in this state, the diffusible hydrogen will increase, and there is a risk of weld cracks occurring. In particular, in on-site welding, it is difficult to prepare multiple drying facilities, and the distance to and from the drying facilities becomes long, resulting in an increase in labor hours. In addition, when transporting the welding rod to the site or handling it during welding, the coating may partially fall off due to impact, making it unusable. For these reasons, there is a strong demand for the development of a low-hydrogen covered metal arc welding electrode that has improved moisture absorption resistance, can be left in the air for long periods of time, and has improved resistance to sheath loss.
[0004] In response to this situation, various proposals have been made as a means of improving moisture absorption resistance and adhesion of the coating. For example, Patent Document 1 discloses a technology related to a covered metal arc welding rod that aims to reduce hydrogen and improve moisture absorption resistance by adjusting the weight ratio of Na2O / K2O, firing in a carbon dioxide gas atmosphere, and containing lithium. However, the technology described in Patent Document 1 has a problem with resistance to sheathing being somewhat insufficient due to insufficient adhesion of the coating.
[0005] On the other hand, Patent Document 2 discloses a technology for a covered electrode with excellent moisture absorption resistance due to AlF3 and LiF. However, the technology described in Patent Document 2 relates to a covered electrode for temporary welding, and it is difficult to use it for actual welding or welded joints.
[0006] In addition, Patent Document 3 discloses a technology for a covered electrode aimed at improving the adhesion of the coating made of hectorite. However, although the technology described in Patent Document 3 has good resistance to falling off, it has a problem with low moisture absorption. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 56-109191 [Patent Document 2] JP 2018-89673 A [Patent Document 3] Japanese Patent Publication No. 57-160597 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been devised in view of the above-mentioned problems, and has an object to provide a low-hydrogen covered metal arc welding electrode having improved properties, particularly, low moisture absorption properties and resistance to sheath falling off properties. [Means for solving the problem]
[0009] The gist of the present invention is (1) In a low-hydrogen covered metal arc welding electrode in which a coating is applied to a steel core wire, the total of one or more metal carbonates: 30 to 55%, the total of one or more metal fluorides: 8 to 20%, the total of one or more of the sum of the Ti oxides converted into TiO2 and the sum of the Zr oxides converted into ZrO2: 2 to 8%, the total of the Si oxides converted into SiO2: 5 to 8%, the total of the Al oxides converted into Al2O3: 0.2 to 1.5%, the total of one or more of the Na oxides and Na fluorides, in mass % relative to the total mass of the coating. The coating agent is characterized in that it contains the following: total of K converted values of one or more of K oxide and K fluoride: 1.1 to 1.5%, total of K converted values of one or more of K oxide and K fluoride: 0.8 to 1.0%, total of Li converted values of one or more of Li oxide and Li fluoride: 0.02 to 0.07%, Si: 2 to 5%, Mn: 1 to 6%, Fe: 4 to 30%, Ti: 0.5 to 2.0%, hectorite: 0.1 to 1.0%, and the remainder is coating agent and impurities, and is applied to a steel core wire at a coverage rate of 25 to 45% by mass relative to the total mass of the low hydrogen covered metal arc welding electrode.
[0010] (2) It also contains Ni, 2. A low hydrogen-based arc welding rod according to claim 1, characterized in that Ni is 12.0% or less, expressed as mass % based on the total mass of the coating material.
[0011] (3) Further containing one or more of metal B, B alloy and B oxide, A low-hydrogen covered metal arc welding rod according to (1) or (2), characterized in that the total of the B-converted values of one or more of metal B, B alloy, and B oxide is 0.10% or less, in mass% relative to the total mass of the coating material.
[0012] (4) Further containing one or both of Cr and Mo, The low hydrogen covered metal arc welding electrode according to any one of (1) to (3) is characterized in that the total content of one or both of Cr and Mo is 6.0% or less, in mass % based on the total mass of the coating material. Effect of the Invention
[0013] According to the low hydrogen type covered metal arc welding electrode of the present invention, it is possible to provide a low hydrogen type covered metal arc welding electrode which has improved moisture absorption resistance and resistance to shedding of the coating, and which has good welding workability and mechanical performance and can provide a high quality welded joint. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In order to solve the above-mentioned problems, the present inventors have conducted detailed studies on the composition of the coating material of a low-hydrogen covered metal arc welding electrode having improved properties of low moisture absorption and resistance to shedding of the coating.
[0015] As a result, it was found that moisture-resistant properties can be obtained by optimizing the contents of Na oxide, Na fluoride, K oxide, K fluoride, Li oxide and Li fluoride in terms of Na, K and Li, and that the resistance to shedding of the coating can be improved by optimizing the content of hectorite. After further investigation, the present invention was completed.
[0016] The reasons for limiting each component in the coating material of the low hydrogen type covered metal arc welding electrode of the present invention will be described in detail below. The content of each component in the low hydrogen type covered metal arc welding electrode is expressed as mass% relative to the total mass of the coating material, and when expressing the mass%, it is simply written as %.
[0017] [Total of one or more metal carbonates: 30-55%] Metal carbonates include calcium carbonate, magnesium carbonate, barium carbonate, etc., and are decomposed by the heat of the arc to generate CO2 gas, which protects the weld metal from the atmosphere. If the total of one or more metal carbonates is less than 30%, the shielding effect is insufficient and blowholes are likely to occur. On the other hand, if the total of one or more metal carbonates exceeds 55%, the arc becomes unstable, the bead shape becomes poor, and the slag removability also becomes poor. Therefore, the total of one or more metal carbonates is set to 30-55%.
[0018] [Total of one or more metal fluorides: 8-20%] Metal fluorides refer to fluorite, magnesium fluoride, aluminum fluoride, etc., and have the effect of adjusting the fluidity of the molten slag to improve the bead shape. If the total of one or more metal fluorides is less than 8%, the fluidity of the molten slag will be poor, the slag encapsulation will be unstable, and the bead shape will be poor. On the other hand, if the total of one or more metal fluorides exceeds 20%, the shape of the sheathing tube will be incomplete, resulting in a one-sided melting state, and the arc will be unstable. Therefore, the total of one or more metal fluorides should be 8-20%.
[0019] [Total of one or both of Ti oxides converted into TiO2 and Zr oxides converted into ZrO2: 2~8%] Ti oxide and Zr oxide are added from rutile, titanium oxide, titanium slag, zircon sand, zirconia, etc., and have the effect of adjusting the viscosity of the molten slag to improve the bead shape. If the total of one or two of the sum of the TiO2 converted values of Ti oxide and the sum of the ZrO2 converted values of Zr oxide is less than 2%, the viscosity of the slag decreases and the bead shape becomes poor. On the other hand, if the total of one or two of the sum of the TiO2 converted values of Ti oxide and the sum of the ZrO2 converted values of Zr oxide exceeds 8%, the viscosity of the molten slag increases and the fluidity of the slag becomes poor, resulting in a poor bead shape. Therefore, the total of one or two of the sum of the TiO2 converted values of Ti oxide and the sum of the ZrO2 converted values of Zr oxide is set to 2 to 8%.
[0020] [Total of silicon oxides converted into SiO2: 5-8%] Silicon oxides are added from silica sand, zircon sand, feldspar, water glass, etc., and have the effect of increasing the viscosity of the molten slag, ensuring slag with appropriate viscosity, and improving the bead shape. If the total of the SiO2 equivalent value of silicon oxides is less than 5%, the viscosity of the molten slag will be low and the bead shape will be poor. On the other hand, if the total of the SiO2 equivalent value of silicon oxides exceeds 8%, the slag will become glassy and the slag removability will be poor. Therefore, the total of the SiO2 equivalent value of silicon oxides should be 5-8%.
[0021] [Total of Al oxides converted to Al2O3: 0.2-1.5%] Aluminum oxide is added from alumina, etc., and has the effect of stabilizing the arc and improving the bead shape. If the total of the Al oxides converted into Al2O3 is less than 0.2%, the arc becomes unstable and the bead shape becomes poor. On the other hand, if the total of the Al oxides converted into Al2O3 exceeds 1.5%, the slag becomes glassy and slag removal becomes poor. Therefore, the total of the Al oxides converted into Al2O3 is set to 0.2-1.5%.
[0022] [Total of one or more of sodium oxides and sodium fluorides converted into sodium: 1.1-1.5%] Na oxide is mainly added from sodium silicate of water glass, etc., and has the effect of improving the paintability during the manufacturing of welding rods and the stability of the arc during welding. It is also added from sodium fluoride and sodium silicofluoride of Na fluorides, and from albite and sodium borate of Na oxides, and is necessary for ensuring welding workability. If the total of the Na equivalent value of one or more of Na oxides and Na fluorides is less than 1.1%, the arc becomes unstable. If the total of the Na equivalent value is less than 1.1%, the paintability during production becomes poor and the resistance to shedding of the coating also decreases. On the other hand, if the total of the Na equivalent value of one or more of Na oxides and Na fluorides exceeds 1.5%, the moisture absorption property decreases, and the arc blow becomes too strong and unstable. Therefore, the total of the Na equivalent value of one or more of Na oxides and Na fluorides is 1.1 to 1.5%.
[0023] [Total of K-equivalent value of one or more of K oxides and K fluorides: 0.8~1.0%] K oxide is mainly added from potassium silicate of water glass, etc., and has the effect of improving the stability of the arc during welding. It is also added from potassium silicofluoride and potassium fluoride of K fluorides, and potassium feldspar of K oxide, and is necessary for ensuring welding workability. If the total of the K-equivalent value of one or more of K oxide and K fluorides is less than 0.8%, the arc becomes unstable. On the other hand, if the total of the K-equivalent value of one or more of K oxide and K fluorides exceeds 1.0%, the hygroscopicity decreases, and the arc blow becomes weak and unstable. Therefore, the total of the K-equivalent value of one or more of K oxide and K fluorides is 0.8 to 1.0%.
[0024] [Total of one or more types of Li oxide and Li fluoride converted into Li: 0.02~0.07%] Li oxide and Li fluoride are added from lithium fluoride, aluminum fluoride, lithium silicate of water glass, etc., and have the effect of improving the moisture absorption resistance of the coating. If the total of the Li equivalent value of one or more of Li oxide and Li fluoride is less than 0.02%, the moisture absorption resistance is not obtained. On the other hand, if the total of the Li equivalent value of one or more of Li oxide and Li fluoride exceeds 0.07%, the moisture absorption resistance is improved, but the drying speed after painting becomes too fast during welding rod manufacturing, causing microcracks on the coating surface, and the resistance to falling off is also reduced. Therefore, the total of the Li equivalent value of one or more of Li oxide and Li fluoride is set to 0.02 to 0.07%.
[0025] [Si: 2-5%] Silicon is added from metal Si, Fe-Si, Fe-Si-Mn, etc., and is used to deoxidize the weld metal, and is also necessary from the viewpoint of welding workability. If the silicon content is less than 2%, deoxidation is insufficient and blowholes are likely to occur in the weld metal. On the other hand, if the silicon content exceeds 5%, low melting point oxides are precipitated at the grain boundaries of the weld metal, reducing the toughness of the weld metal. Therefore, the silicon content is set to 2-5%.
[0026] [Mn: 1-6%] Mn is added as metallic Mn, Fe-Mn, Fe-Si-Mn, etc., and is important as a deoxidizer like Si, and has the effect of refining the weld metal structure and increasing the toughness and strength of the weld metal. If Mn is less than 1%, the strength and toughness of the weld metal will decrease. Also, if Mn is less than 1%, deoxidization will be insufficient and blowholes will easily occur in the weld metal. On the other hand, if Mn exceeds 6%, the hardenability will be strongly affected and the toughness of the weld metal will decrease. Therefore, Mn is set to 1 to 6%.
[0027] [Fe: 4-30%] Fe is added from iron powder, iron alloy powder such as Fe-Mn or Fe-Mo, or iron oxide, and has the effect of lowering the potential gradient of the arc, shortening the arc length, and preventing one-sided melting of the coating material. Fe also has the effect of improving work efficiency by increasing the amount of deposition. If Fe is less than 4%, the arc length becomes long, the arc is likely to disappear during welding, one-sided melting of the coating material occurs, and the arc becomes unstable. On the other hand, if Fe exceeds 30%, the amount of slag material decreases, the slag coverage becomes uneven, and the bead shape becomes poor. Therefore, Fe should be 4-30%.
[0028] [Ti: 0.5~2.0%] Ti is added from metallic Ti, Fe-Ti, etc., and is effective as a deoxidizer, and at the same time, has the effect of lowering the potential gradient of the arc and stabilizing the arc. Ti also has the effect of refining the microstructure of the weld metal and improving its toughness. If Ti is less than 0.5%, the microstructure of the weld metal is not refined, and the toughness of the weld metal decreases. On the other hand, if Ti exceeds 2.0%, the precipitation of Ti oxide in the weld metal increases, and the toughness of the weld metal decreases. Therefore, Ti is set to 0.5 to 2.0%.
[0029] [Hectorite: 0.1-1.0%] Hectorite is a type of clay mineral that contains Na 0.3 (MgLi)3Si4O 10 It has a composition of (F,OH)2. Hectorite has good dispersibility in the coating agent, and increases the viscosity of the coating agent during production, preventing scratches and chipping immediately after painting and improving paintability. Hectorite also improves the adhesion of the coating agent and improves its resistance to falling off. If the hectorite content is less than 0.1%, the paintability and resistance to falling off cannot be obtained. On the other hand, if the hectorite content exceeds 1.0%, the paintability is good and the coating agent does not fall off, but the coating tube becomes too strong, the arc voltage increases during welding, making the arc more likely to break and the arc unstable. Therefore, the hectorite content is 0.1 to 1.0%.
[0030] [Coating rate: 25-45% by mass of coating material relative to the total mass of low-hydrogen covered metal arc welding electrode] The coverage rate of the coating material on the outer circumference of the steel core wire has a large effect on the shielding resistance during welding. If the coverage rate is less than 25% by mass (hereinafter simply referred to as %) of the coating material relative to the total mass of the low-hydrogen covered metal arc welding electrode, the amount of coating material itself will be reduced, resulting in insufficient shielding, and the N content in the weld metal will increase, reducing the toughness of the weld metal. On the other hand, if the coverage rate of the coating material exceeds 45%, the amount of slag will be excessive and the arc will become unstable. Therefore, the coverage rate is set to 25 to 45%.
[0031] [Ni:12.0% or less] Ni is added from metallic Ni and is an element that improves the strength and toughness of the weld metal. On the other hand, if Ni exceeds 12.0%, the toughness of the weld metal decreases. Therefore, Ni content is set to 12.0% or less.
[0032] [Total of B-converted values of one or more of metal B, B alloy and B oxide: 0.10% or less] B is added from metal B, Fe-B, Fe-Mn-B, borax, colemanite, etc., and is an element that is effective in improving hardenability and suppressing the formation of grain boundary ferrite in small amounts, and is effective in improving the toughness of the weld metal. On the other hand, if the total of the B-equivalent values of one or more of metal B, B alloy, and B oxide exceeds 0.10%, the toughness of the weld metal decreases. Therefore, the total of the B-equivalent values of one or more of metal B, B alloy, and B oxide should be 0.10% or less.
[0033] [Total of Cr and Mo: 6.0% or less] Cr is added as metallic Cr, Fe-Cr, etc., and Mo is added as metallic Mo, Fe-Mo, etc., and has the effect of further improving the strength of the weld metal. On the other hand, if the total of one or both of Cr and Mo exceeds 6.0%, the toughness of the weld metal decreases. Therefore, the total of one or both of Cr and Mo is set to 6.0% or less.
[0034] The coating material of the low hydrogen type covered metal arc welding electrode of the present invention is the impurities contained in the coating material and the alloy powder as the balance other than the above-mentioned components.
[0035] The coating agent is contained from the viewpoint of productivity, and the content of the coating agent is, for example, 0.1 to 1.0%.
[0036] Impurities are components contained in raw materials or components mixed in during the manufacturing process, but are not intentionally contained in the coating. Impurities contained in coatings include organic matter, alloy powder, and P and S contained in paints. The total amount of impurities is preferably 2% or less, more preferably 1% or less.
[0037] Examples of the steel core wire used include JIS G3523 SWY11, mild steel, and low alloy steel. The P content of the steel core wire is 0.010% or less because it reduces toughness, S content is 0.010% or less because it reduces the fluidity of the slag, and N content is 0.01% or less because it has a strong bond with B and reduces hardenability. EXAMPLES
[0038] The effects of the present invention will now be described in more detail with reference to examples.
[0039] In this example, a welding rod coating machine was used to coat a steel core wire having a diameter of 4 mm and a length of 400 mm, and having the composition shown in Table 1, with a coating agent having the composition shown in Tables 2 and 3 at the coverage shown in Table 2, and then the wire was dried to produce various low-hydrogen covered electrodes.
[0040] In addition, in Tables 1, 2 and 3, the notation "-" means that the component is not intentionally included.
[0041] [Table 1]
[0042] [Table 2]
[0043] [Table 3]
[0044] The manufactured welding rods were examined for moisture absorption, diffusible hydrogen, coating loss rate, welding workability, mechanical performance and welding defects.
[0045] [Moisture absorption amount] The moisture resistance was evaluated based on the amount of moisture absorbed. After drying the welding rod at 350℃ for 1 hour, it was left in a thermo-hygrostat chamber maintained at a temperature of 30℃ and a humidity of 80% for 7 hours. The weight percentage of the coating before and after drying was measured, and those within 0.4% were considered good.
[0046] [Diffusible hydrogen content] To measure the amount of diffusible hydrogen, a welding rod was used that had been dried at 350℃ for 1 hour, and then left for 7 hours in a constant temperature and humidity chamber maintained at a temperature of 30℃ and a humidity of 80%. Welding was performed with alternating current polarity, a welding current of 160A, and a welding speed of 18cm / min. The amount of diffusible hydrogen was measured according to JIS Z 3118, and a value of 8ml / 100g or less was considered good.
[0047] [Coating loss rate] The resistance to shedding was evaluated based on the percentage of shedding of the coating. A welding rod weighing about 1.5 kg was placed in a 55 mm x 300 mm x 500 mm steel box made of 6 mm thick plate, and the box was rotated for 5 minutes at a speed of 40 revolutions per minute around its longitudinal axis, and the weight percentage of the shedding of the coating was measured. A shedding rate of less than 2.0% was considered good.
[0048] [Welding workability] The welding workability was evaluated using JIS G 3106 SM490A steel plates with a thickness of 16 mm, width of 100 mm, and length of 450 mm. Flat, horizontal fillet, and vertical upward welding were performed using AC welding, and a comprehensive sensory evaluation was performed.
[0049] (Arc state) The welding was judged to be good when the arc was stable during welding, the arc did not disappear during welding, a constant arc length was obtained, and there was no disturbance in the straightness of the arc.
[0050] (Bead shape) Welds with both toes aligned and with consistent weld height, bead width, waviness and surface condition were deemed good.
[0051] (Slag fluidity) A good condition was determined when a healthy molten pool was obtained during welding, the molten slag did not penetrate into the molten pool, and the molten slag did not come into contact with the tip of the welding rod.
[0052] (Slag removability) After welding, when the solidified slag was struck with a chipping hammer, if the slag cracked and could then be easily removed, it was judged to be good.
[0053] [Evaluation of machine performance] Using JIS G 3106 SM490A steel plate with a thickness of 20 mm, weld metal test specimens were prepared in accordance with JIS Z 3211, using AC current polarity, a welding current of 150 to 170 A, and a preheat / interpass temperature of 90 to 110°C.
[0054] The mechanical performance was evaluated based on the tensile strength of the weld metal and the absorbed energy in a Charpy impact test at -20°C. A tensile strength of 490 MPa or more and an absorbed energy of 80 J or more were rated as good.
[0055] [Welding defects] For weld defects (blowholes, etc.), defects in the weld metal were judged using JIS Z 3104 "Radiation Testing Method for Steel Welded Joints" before mechanical test pieces were taken. From the radiographic photographs, it was determined which of the 1st to 4th types of defects in "Annex 4 Table 1 Types of Defects" the defect fell under, and in "6. Classification of Defects" the defects were classified into Classes 1 to 4. Of these, Class 1 was A, Class 2 was B, Class 3 and Class 4 was C, with A and B being good and C being bad.
[0056] These analysis results and survey findings are summarized in Table 4.
[0057] [Table 4]
[0058] In Tables 2, 3, and 4, welding rods No. 1 to No. 27 are examples of the present invention, and welding rods No. 28 to No. 48 are comparative examples. Welding rods No. 1 to No. 27, which are examples of the present invention, have appropriate amounts of the total of metal carbonates, the total of metal fluorides, the total of Ti oxides in terms of TiO2 and the total of Zr oxides in terms of ZrO2, the total of Si oxides in terms of SiO2, the total of Al oxides in terms of Al2O3, the total of Na oxides and Na fluorides in terms of Na, the total of K oxides and K fluorides in terms of K, the total of Li oxides and Li fluorides in terms of Li, Si, Mn, Fe, Ti, and hectorite, and the coating rate of the coating agent is appropriate, so that the amount of moisture absorption and the amount of diffusible hydrogen are low, the rate of shedding of the coating is low, the arc is stable, the bead shape is good, and the slag fluidity and slag removability are good. The tensile strength and absorbed energy of the weld metal were both good, and there were no welding defects in the weld metal, which was a satisfactory result.
[0059] Welding rod No. 10 contains an appropriate amount of Ni and the total B-equivalent value of one or more of metal B, B alloy, and B oxide, so the tensile strength of the weld metal was 700 MPa or more and the absorbed energy was 170 J or more.
[0060] Welding rod No. 14 contains an appropriate amount of Ni, Cr, and / or Mo. Therefore, even if the deposited metal exhibits a high tensile strength of 780 MPa or more, the absorbed energy of the deposited metal is 80 J or more.
[0061] Welding rod No. 17 contains an appropriate amount of Ni, the total of one or more of the B-equivalent values of metal B, B alloy, and B oxide, and the total of one or more of Cr and Mo. Therefore, even though the tensile strength of the weld metal is high at 780 MPa or more, the absorbed energy of the weld metal is high at 152 J, which is an extremely satisfactory result.
[0062] Welding rods No. 22 and No. 24 contain an appropriate amount of Cr and / or Mo, and therefore the tensile strength of the deposited metal was 700 MPa or more.
[0063] Welding rods No. 23 and No. 25 contain an appropriate amount of Ni added to the weld metal, so the tensile strength of the weld metal was 700 MPa or more and the absorbed energy of the weld metal was 150 J or more.
[0064] Welding rods No. 26 and No. 27 contain an appropriate amount of the total B-converted value of one or more of metal B, B alloy, and B oxide, and therefore have an absorbed energy of 150 J or more.
[0065] In the comparative example, welding rod No. 28 had a large total SiO2 equivalent value, so the slag became glassy and the slag removability was poor. Also, because it had a small amount of Fe, the arc length became long, the arc was easily lost during welding, the coating melted on one side, and the arc was unstable.
[0066] Welding rod No. 29 has a high total Al2O3 equivalent value, so the slag becomes glassy and slag removal is poor.
[0067] Since the welding rod No. 30 had a small total amount of metal fluorides, the fluidity of the molten slag was poor, the slag encapsulation was unstable, and the bead shape was poor.
[0068] Welding rod No. 31 had a poor bead shape because the total SiO2 equivalent value was low. Also, the total B equivalent value of one or two of metal B, B alloy, and B oxide was high, so the absorbed energy of the weld metal was low.
[0069] Welding rod No. 32 had a high total metal fluoride content, so it melted only on one side and the arc was unstable.
[0070] Welding rod No. 33 had a low total of TiO2 and ZrO2, which reduced the viscosity of the slag and resulted in poor bead shape. Also, the total of Cr and Mo was high, which resulted in low absorbed energy of the weld metal.
[0071] Welding rod No. 34 had a high total amount of metal carbonates, which caused the arc to become unstable, resulting in poor bead shape and poor slag removability.
[0072] Welding rod No. 35 had a low total Al2O3 content, which resulted in an unstable arc and poor bead shape. Also, because it had a low Si content, blowholes occurred in the deposited metal.
[0073] Welding rod No. 36 had a low total metal carbonate content, which caused blowholes. Also, because it had a high Ni content, the absorbed energy of the weld metal was low.
[0074] Welding rod No. 37 had a high total of one or both of the TiO2 and ZrO2 converted values, which resulted in poor slag fluidity and poor bead shape.
[0075] Welding rod No. 38 had a high total Na content of one or more of sodium oxides and sodium fluorides, so it had a high moisture absorption and diffusible hydrogen content, and the arc was too strong and unstable. Also, because it had a high Si content, the absorbed energy of the weld metal was low.
[0076] Welding rod No. 39 had a small total Li-equivalent value of one or more of Li oxide and Li fluoride, and therefore had a large amount of absorbed moisture and diffused hydrogen.
[0077] Welding rod No. 40 had a low total Na content of one or more of Na oxides and Na fluorides, so the arc was unstable and the coating loss rate was high. Furthermore, the deposited metal had a low absorbed energy because it contained a large amount of Ti.
[0078] Welding rod No. 41 had a large total K-equivalent value of one or more of K oxide and K fluoride, so it had a large amount of absorbed moisture and diffused hydrogen, and the arc spray was weak and unstable. Also, because it had a large amount of Mn, the absorbed energy of the weld metal was low.
[0079] Welding rod No. 42 had a high total Li-equivalent value of one or more of Li oxides and Li fluorides, so the rate of sheath loss was high. In addition, because it had a low Mn content, blowholes occurred in the weld metal, and the tensile strength and absorbed energy of the weld metal were low.
[0080] Welding rod No. 43 had an unstable arc because the total K-equivalent value of one or more of K oxide and K fluoride was low. Also, because it had a low Ti content, the absorbed energy of the weld metal was low.
[0081] Welding rod No. 44 contains a large amount of Fe, which causes the slag to be unevenly coated and results in a poor bead shape.
[0082] Welding rod No. 45 contains a lot of hectorite, so the arc voltage rose during welding, causing arc interruption and making the arc unstable.
[0083] Welding rod No. 46 had a low coverage rate, so the absorbed energy of the weld metal was low.
[0084] Welding rod No. 47 had a high rate of sheathing loss because it contained less hectorite.
[0085] The arc of welding rod No. 48 was unstable because of its high coverage.
Claims
1. In low-hydrogen covered electrodes in which a coating is applied to the steel core wire, The coating agent is, in mass % based on the total mass of the coating agent, Total of one or more metal carbonates: 30 to 55%, Total of one or more metal fluorides: 8 to 20%, Ti oxide TiO 2 The sum of the converted values and ZrO 2 Sum of one or two types of conversion value: 2 to 8%; Silicon oxide SiO 2 Total conversion value: 5-8% Al oxide Al 2 O 3 Total conversion value: 0.2-1.5%, Sum of one or more of Na oxides and Na fluorides in terms of Na: 1.1 to 1.5%, The total of one or more of K oxides and K fluorides converted into K: 0.8 to 1.0%; The total of one or more of Li oxides and Li fluorides converted into Li: 0.02 to 0.07%; Si: 2 to 5%, Mn: 1 to 6%, Fe: 4 to 30%, Ti: 0.5-2.0%, Hectorite: 0.1-1.0%, A low-hydrogen covered metal arc welding rod, characterized in that a coating material, the balance of which is impurities, is applied to a steel core wire at a coverage rate of 25 to 45% by mass based on the total mass of the low-hydrogen covered metal arc welding rod.
2. Further containing Ni, In mass % based on the total mass of the coating material, 2. The low hydrogen type covered metal arc welding electrode according to claim 1, characterized in that Ni: 12.0% or less.
3. Further containing one or more of metal B, B alloy and B oxide, In mass % based on the total mass of the coating material, 3. The low hydrogen type covered metal arc welding electrode according to claim 1, wherein the total of the B converted values of one or more of metal B, B alloy and B oxide is 0.10% or less.
4. Further containing one or both of Cr and Mo, In mass % based on the total mass of the coating material, The low hydrogen type covered metal arc welding electrode according to any one of claims 1 to 3, characterized in that the total content of one or both of Cr and Mo is 6.0% or less.
Citation Information
Patent Citations
Production of low hydrogen type coated arc electrode
JP1981109191A
Manufacture of covered electrode
JP1982052594A
Manufacture of low-hydrogen type coated electrode
JP1982160597A
Low hydrogen type tacking covered electrode
JP2018089673A
Arc welding rod coated with low hydrogen-based coating agent for crude oil tank steel
JP2020189302A